Tourism Suitability Index Assessment and Development Strategy in Werahung Beach, Ambon City, Maluku - Elisecarmel, Sionivena Meyske; Astina, I Komang; Sihasale, Daniel Anthoni (Indonesian Journal of Tourism and Leisure, 2025)
Tourism is a strategic sector that plays an important role in economic growth, job creation, and improving community welfare. Werahung Beach is one of the beaches in Ambon City that offers stunning natural scenery and has the potential to be a major attraction for tourists. This study aims to evaluate the level of tourism suitability and identify sustainable tourism development strategies based on physical and social aspects to formulate appropriate development recommendations. The data collected includes the results of the Tourism Suitability Index (TSI) analysis used to evaluate the suitability of the area based on physical parameters and SWOT data used to determine the development strategy for Werahung Beach. The research method used in this study is a mixed method with data collection techniques through field observation and documentation. The results of the study showed the TSI value for each station as follows: Station I (71.87%), Station II (69.53%), and Station III (65.62%). Werahung Beach has a total IT value of 69%, which is included in the S3 category (Quite Suitable). The SWOT analysis shows that the development strategy for Werahung Beach is in Quadrant III with IFAS (0.53) and EFAS (0.33).